New Azopolyimides: Synthesis and Film Studies - Kaniakumari, Devi; Rajendiran, T.V. (Asian Journal of Chemistry, 2010)
Aromatic azopolyimide films were prepared from 3,3',4,4'- azobenzenetetracarboxylic dianhydride condensed with four different diamines by thermal imidization method. Diamines used were (i) 4,4'- diaminodiphenyl ether, (ii) 4,4'-diaminodiphenyl methane (iii) 4,4'- diamino benzanilide and (iv) 2,2-bis[4(p-amino phenoxy)phenyl]-propane. These polyimide films were characterized by scanning electron microscope, X-ray diffraction, pyrolysis-mass spectra and dielectric constant.